A state-wide assessment of the association between epidural analgesia, maternal fever and neonatal antibiotics in Colorado, 2007–2012. Issue 2 (24th June 2016) - White, Alice; Olson, Daniel; Messacar, Kevin
Abstract : Objective: To determine if an association exists between epidural analgesia, maternal fever and neonatal antibiotic exposure in a state-wide birth cohort. Design, setting and participants: We performed a retrospective cohort study of the population-based Colorado Department of Public Health and Environment birth certificate database. Data included all reported births in the state of Colorado between 2007 and 2012. Live, non-preterm, vaginal, singleton, in-hospital births were included in analysis. Exposure: Maternal epidural analgesia and maternal fever. Main outcomes measures: Neonatal antibiotic treatment for suspected sepsis. A stratified analysis was conducted to evaluate whether epidural use was an effect modifier of the association between maternal fever and neonatal antibiotic treatment. Results: The final cohort included 261 457 births. 2.2% of women who received an epidural had a fever, as compared with 0.4% of women who did not receive an epidural (OR: 5.4; 95% CI 4.9 to 6.0), and neonates born to women who received an epidural had 1.26 times increased odds of antibiotic treatment (95% CI 1.1 to 1.4). Stratification by epidural use did not alter the association between maternal fever and neonatal antibiotic treatment. Conclusions: Colorado providers treat neonates born to mothers with maternal fever without respect to whether the mother had an epidural. Further research into improved criteria for neonatal sepsis evaluation that accounts for the contribution of maternal epidural fever should be developed to decrease unnecessary neonatal antibiotic exposure.